Hubungan Kecemasan Dengan Health Seeking Behavior Pada Masa Pandemi Covid-19 - lita lita; Hari Guspian; Susi Erianti (Jurnal Kesehatan Komunitas, 2022)
The pandemic situation due to the 2019 Coronavirus Disease (COVID-19) has an impact on anxiety for all people in Indonesia, thus affecting Health-Seeking Behavior (HSB). This study aims to determine the relationship between anxiety and health-seeking behavior during the COVID-19 pandemic. The type of research used is quantitative, with a Cross-Sectional approach. The test used is Chi-Square to see the relationship between anxiety and health-seeking behavior during the COVID- 19 pandemic. The sample was 171 people using a proportional random sampling technique. The results showed that the average age was 38.08 years, and the majority were female, married, in high school, self-employed, BPJS health insurance. The level of mild anxiety was 51 (29.8%) while there was no anxiety, moderate anxiety, and severe anxiety was 40 (23.4%). Health Seeking Behaviors for Health Workers/Midwives/Mantri/Physicians/Access to Health care Public health center/Hospital 115 (67.3%), buying drugs at stalls/pharmacies/drug stores 33 (19.3%), making herbs/buying herbs/herbs 19 (11.1 %) and did nothing/ did not take any action 4 (2.3%). The test results obtained P-value = 0.058 (> 0.05), meaning that there is no relationship between anxiety and health-seeking behavior during the COVID-19 pandemic. It is hoped that the community will not be anxious to go to health services for the creation of better public health behavior.